Negative feedback regulation of calcineurin-dependent Prz1 transcription factor by the CaMKK-CaMK1 axis in fission yeast - Cisneros-Barroso, Eugenia (Oxford University Press, 2014)
Calcium signals trigger the translocation of the Prz1 transcription factor from the cytoplasm to the nucleus. The process is regulated by the calcium-activated phosphatase calcineurin, which activates Prz1 thereby maintaining active transcription during calcium signalling. When calcium signalling ceases, Prz1 is inactivated by phosphorylation and exported to the cytoplasm. In budding yeast and mammalian cells, different kinases have been reported to counter calcineurin activity and regulate nuclear export. Here, we show that the Ca(2+)/calmodulin-dependent kinase Cmk1 is first phosphorylated and activated by the newly identified kinase CaMKK2 homologue, Ckk2, in response to Ca(2+). Then, active Cmk1 binds, phosphorylates and inactivates Prz1 transcription activity whilst at the same time cmk1 expression is enhanced by Prz1 in response to Ca(2+). Furthermore, Cdc25 phosphatase is also phosphorylated by Cmk1, inducing cell cycle arrest in response to an increase in Ca(2+). Moreover, cmk1 deletion shows a high tolerance to chronic exposure to Ca(2+), due to the lack of cell cycle inhibition and elevated Prz1 activity. This work reveals that Cmk1 kinase activated by the newly identified Ckk2 counteracts calcineurin function by negatively regulating Prz1 activity which in turn is involved in activating cmk1 gene transcription. These results are the first insights into Cmk1 and Ckk2 function in Schizosaccharomyces pombe.